2013
DOI: 10.4028/www.scientific.net/kem.537.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Fracture Strength of Freestanding Diamond Films

Abstract: Preparation of freestanding Ge(100) thin films using plasmaenhanced chemical vapor deposition J. Vac. Sci. Technol. A 3, 692 (1985); 10.1116/1.573286 Freestanding thin film Ge single crystals grown by plasmaenhanced chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…3, further discovery is same as the content in literature [7], it is indicated that the depth of the concrete carbonization is a random distribution with time. As the literature [8] pointing out that there is no certain relationship between compressive strength and rebound value of concrete.…”
Section: Discussionmentioning
confidence: 99%
“…3, further discovery is same as the content in literature [7], it is indicated that the depth of the concrete carbonization is a random distribution with time. As the literature [8] pointing out that there is no certain relationship between compressive strength and rebound value of concrete.…”
Section: Discussionmentioning
confidence: 99%